El proceso comunicativo en la educación virtual en la carrera de Comunicación Social de la UTB - De La Paz Gonzabay, Bryan Vicente (2021)
The purpose of the following work was to analyze the communication process in virtual education within the social communication career of the UTB, to achieve this it was carried out in a "case study", which will allow us to investigate the forms used for interaction and communication in the virtual environment during the academic period. After a review within the field of communication on the subject, this case study discusses some aspects that facilitate the communicative process and the construction of collaborative learning in a virtual environment. Communication and interaction seeks to promote the stimulation of a learning process, while recognizing that the virtual classroom is at a disadvantage in relation to the face-to-face classroom given that the communication possibilities we have when we can interact face to face with the participants in the educational environment . In the virtual environment, communication promotes the development of learning, which favors students when establishing common goals, interaction between groups, strengthening interpersonal relationships that develop within the classroom. The purpose of the work is to design an improvement in the communication process in the virtual education of the social communication career at the UTB, to achieve it, both quantitative and qualitative methodologies were used.